Brazilein in combination with cisplatin inhibit proliferation and migration on highly metastatic cancer cells, 4T1 - Sri Handayani; Ratna Asmah Susidarti; Zalinar Udin; Edy Meiyanto; Riris Istighfari Jenie (Universitas Gadjah Mada, 2016)
Brazilein performs anticancer activities on several cancer cells and potentially inhibits metastasis. The aims of this study is to observe the synergistic cytotoxic and migration inhibitory effect of brazilein combined with cisplatin on 4T1 breast cancer cells. Under MTT assay, we found that brazilein revealed cytotoxic effect on 4T1 cells in a dosedependent manner (IC50=50 ± 0.3 µM). Combination of brazilein and cisplatin showed synergistic effect (CI=0.72). Flowcytometry analysis on the cell cycle progression showed that single treatment of 25 µM brazilein induced G2/Mphase accumulation, 12.5 µM cisplatin induced Sphase accumulation, while combination of brazilein and cisplatin induced Sphase and G2/Mphase accumulation. Combination of brazilein and cisplatin induced apoptosis higher than that of the single treatments. Based on wound healing assay, 12.5 µM brazilein and its combination with 6.25 µM cisplatin inhibited cells migration. Immunoblotting and gelatin zymography analysis showed that combination of brazilein and cisplatin inhibited the expression level of Rac1 and MMP9 proteins. Based on these results, we conclude that brazilein enhanced cytotoxic activity of cisplatin and inhibited migration on 4T1 cells and potentially can be developed as an enhancing cytotoxic and antimetastasis agent.